PENGARUH BUDAYA ORGANISASI, KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA KARYAWAN SWALAYAN ADA MAJAPAHIT SEMARANG) - Yohana Novia Saputri, 15.05.51.0072; Waruwu, Penunjang (Students' Journal of Economic and Management, 2019)
This study aims to discuss and analyze the influence of culture, job satisfaction and organizational commitment on the performance of ADA Majapahit Semarang supermarket employees. The population in this study is ADA Majapahit Semarang supermarket company, because the participation of research is very large, this study took a sample of 97 respondents. The technique of taking samples in this study using purposive sampling, namely sampling techniques using Slovin.The data used in this study is primary data, with a questionnaire as a research instrument. The analytical tool used is multiple linear regression, validity test, reliability test, F test, coefficient of determination test (R²), and t test, which is then processed by calculation of SPSS (Statistical Products and Solutions) version 19.The results showed that organizational culture had a positive and significant effect on employee performance, positive and significant job satisfaction on employee performance, organizational commitment significantly increased positively towards employee performance.